Research of preventive maintenance effect on reliability of fault-tolerant uninterruptible power supply - Мандзій, Богдан Андрійович; Волочій, Богдан Юрійович; Озірковський, Леонід Деонісійович; Кузнєцов, Дмитро Сергійович; Кулик, Ігор Володимирович (Eastern-European Journal of Enterprise Technologies, 2013)
Research of preventive maintenance effect on reliability of fault-tolerant uninterruptible power supply is important in determination of the requirements for maintenance. In this paper the objects under consideration are two variants of the fault-tolerant system for uninterruptible power supply with (N+M) and 2×(N+M) redundant configurations, which are provided by preventive maintenance. There are given reliability models for both configurations of faulttolerant system for uninterruptible power supplies, which allows investigating the dependence of their reliability on the frequency of preventive maintenance, in this paper. Reliability models for fault-tolerant systems are formed as graphs of states and transitions. Determination of the reliability parameters is associated with the solution of system of Kolmogorov Chapman differential equations, formed according to the developed graphs. These models are useful both at the design stage (to determine the structure of the fault-tolerant system) and during operation (to determine the requirements for maintenance) of uninterruptible power supply, designed as a fault-tolerant system.